Herbert Gintis, Samuel Bowles, Robert Boyd y Ernst Fehr (Eds.): Moral Sentiments and Material Interests: The Foundations of Cooperation in Economic Life. MIT Press, Cambridge, 2005 - Salcedo M, Jorge Luis (Foro Interno, 2007)
Sin resumen